On the effect of feedstock preparation on the characteristics of warm formed powder compacts - Rahman M.M.; Wardi M.A.S.; Nor S.S.M. (Universiti Malaysia Pahang, 2023)
Powder compaction technology has advanced significantly over the past decades and is considered as an alternative lower-cost process to machining, casting, stamping, forging and other similar metal-working technologies. Feedstock preparation is considered a vital step in producing parts through the powder route because any inhomogeneity within the powder mass would cause inhomogeneous density distribution inside the green compacts, which in turn would cause fracture in the final products after sintering in the controlled environment. This paper presents the outcomes of an experimental investigation on the effects of feedstock preparation on the mechanical properties and microstructures of final products formed at above ambient temperature. A lab-scale uni-axial die compaction rig was designed and fabricated which enabled powder forming at elevated temperatures. Iron powder ASC 100.29 was mechanically mixed with different quantities of zinc stearate for 10, 30, and 60 minutes, respectively. Green compacts were generated by forming the prepared feedstock at 180C through simultaneous upward and downward axial loading. The defect-free green compacts were subsequently sintered in an argon gas fired furnace and characterized for their physical and mechanical properties, and their microstructures were evaluated. The results revealed that the characteristics of the final products were affected by the feedstock preparation. The most suitable lubricant content and mixing time are found to be 0.4 wt% and 60 minutes, respectively. From this study, the proper zinc stearate content and mixing time were identified for the production of high quality products through the warm forming route. This study could be extended by using different types of base powder as well as lubricant. Universiti Malaysia Pahang.